IMPLEMENTASI PRAKTIK KEPENDIDIKAN MAHASISWA PENDIDIKAN EKONOMI DI SMA NEGERI 1 MERANGIN - Elda Afriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational Practice is an integral part of the process of developing the competencies of prospective professional teachers, because it provides students with the opportunity to apply the theories learned in lectures to real-life practice in the school environment. This activity aims to provide students with direct experience in understanding the dynamics of the learning process, classroom management, planning and implementation of learning, as well as patterns of social interaction between teachers, students, and the school community. The method used in this study is a qualitative descriptive approach with data collection techniques in the form of observation, documentation, and student reflection during the implementation of Educational Practice. The results of the study indicate that Educational Practice activities make a significant contribution to improving students' pedagogical competence, especially in the ability to design and implement effective and contextual learning. In addition, students' professional competence also develops through mastery of teaching materials and the application of various learning methods and media. Thus, Educational Practice has a positive impact on the readiness of Economic Education students to face the dynamic, adaptive, and innovative world of education.